Staffing levels at KwaZulu-Natal district hospitals: is the University of KwaZulu-Natal training for the needs of the province? - Andrew Ross; Dumsani Gumede; Solange Mianda (South African Family Practice)
Background: Universities have a social responsibility to ensure that they select and train healthcare professionals (HCPs) who can meet the healthcare needs of local communities. The aim of this study was to assess the extent to which the University of KwaZulu-Natal (UKZN) contributes to the training of HCPs working in district hospitals (DHs) in KwaZulu-Natal Province, and the impact that the funding source for their training has on DH staffing. Methods: This was an observational descriptive study, with all doctors, dentists, dental therapists, pharmacists, physiotherapists and radiographers working at DHs in KZN in November 2016 being invited to participate. Data were collected through a validated questionnaire. Results: A total of 514 HCPs working in 29 DHs participated in the study; over half (57%) of the South African medical graduates had trained at UKZN, as had 62% of pharmacists, 64% of physiotherapists and 92% of dental therapists. Some 87% of the HCPs had worked in DHs for five years or less, 65% planned to leave in the near future, and 29% planned to leave at the end of 2016. Discussion: UKZN plays a significant role in training for the short-term needs of DHs in KZN. Much of the workforce is young and transient, which has implications for service provision and expanding the teaching platform to DHs. The lack of long-term staff retention suggests that UKZN needs to continually monitor the selection of students, as well as the content and context of the training, if it is to contribute to the province’s long-term staffing needs.